Melayani dengan Hati: Esensi Kepemimpinan Kristen yang Sejati - Siar, Devina; Aror, Tesalonika; Kaehe, Agita; Saosang, Jondris (Institut Agama Kristen Negeri Manado, 2024)
Leadership is a great responsibility in which you must have integrity, empathy and wisdom. In the scope of Christianity, the definition of leadership does not only include supervising or directing but also about how to serve with sincerity and wholeheartedness. The essence of true Christian leadership is also to show how to serve with a high degree of totality and love in accordance with the character of Jesus Christ. A true leader is also seen from how he shows humility when serving and in his personal life as a social society